THE IMPORTANCE OF MENTAL HEALTH IN THE WORKPLACE - Kalinin , Andrii (Collection of scientific papers «ΛΌГOΣ», 2022)
Since 2015 the notion of mental health in the workplace has been gradually gaining popularity in the Ukrainian business environment. During the COVID-19 pandemic and war period in Ukraine, the topic about mental health of employees has been taken a significant place in the top discussions of HR managers and directors. HR professionals understand connections between business indicators and mental health, well-being of their employees. In the conditions of competition in the labor market, the objective need for employees to turn to their own health is the fundamental basis of their well-being, competence, resilience and competitiveness.